Prescribing trends of fixed dose combinations in a tertiary care teaching hospital of Bhopal district - Sankdia, Rajanish Kumar; Agrawal, Mehul (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Medicines are an integral part of healthcare. More than one drug is frequently used for treatment of either single ailment or multiple co-morbid conditions. Sometimes, two or more drugs are combined in a fixed ratio into a single dosage form, which is termed as fixed dose combinations (FDCs). Methods: This prospective observational study was carried out in the patients admitted in various medical and surgical wards of Chirayu hospital associated with Chirayu medical college of Bhopal district for a period of 3 months. The prescribed FDCs were collected from the case sheet of the admitted patients. Patients of all ages and both sexes were included in the study. Results: The total numbers of prescriptions from teaching hospital were 475, out of which 373 patients (78.52%) were prescribed FDCs. The first four most preferred FDCs were B complex preparations followed by pantoprazole + domperidone, Diclofenac+Paracetamol and Chlorpheniramine+Pseudo-ephedrine+Paracetamol. Conclusions: In present study total 11types of FDCs were prescribed, out of 11 FDCs prescribed; only 1 type was enlisted in the essential drug list of WHO and Govt. of India. In only 4 types of FDCs there is scientific justification for combining ingredients. Most of FDCs do not have scientific justification for combining the ingredients. It is the need of the time that hospitals should constitute drugs and therapeutics review committees to promote rational prescription of FDCs.